Tryptophan introduction can change β-glucan binding ability of the carbohydrate-binding module of endo-1, 3-β-glucanase. Issue 5 (4th May 2017) - Miki, Ayako; Inaba, Satomi; Maruno, Takahiro; Kobayashi, Yuji; Oda, Masayuki
Abstract: Endo-1, 3-β-glucanase from Cellulosimicrobium cellulans DK-1 has a carbohydrate-binding module (CBM-DK) at the C-terminal side of a catalytic domain. Out of the imperfect tandem α-, β-, and γ-repeats in CBM-DK, the α-repeat primarily contributes to β-glucan binding. This unique feature is derived from Trp273 in α-repeat, whose corresponding residues in β- and γ-repeats are Asp314 and Gly358, respectively. In this study, we generated Trp-switched mutants, W273A/D314W, D270A/W273A/D314W, W273A/G358W, and D270A/W273A/G358W, and analyzed their binding abilities toward laminarioligosaccharides and laminarin. While the binding affinities of D270A/W273A and W273A mutants were either lost or much lower than that of the wild-type, those of Trp-switched mutants recovered, indicating that a Trp introduction in β- or γ-repeat can substitute the α-repeat by primarily contributing to β-glucan binding. Thus, we have successfully engineered a CBM-DK that binds to laminarin by a mechanism different from that of the wild-type, but with similar affinity. Abstract : :